2020
DOI: 10.22460/project.v3i3.p379-383
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Error in Using Simple Present Tense

Abstract: This research aimed to analyse the errors in using simple present tense. Descriptive qualitataive approach was used in this reserch. The subject of this research was 37 management students of Economic Faculty  Muslim Nusantara Al Washliyah University  Medan. The data were the sudents’  answer test.  This research was analysed by Surface strategy taxonomy proposed by Dulay et al. The results of the research showed that there are four types of students’ errors in using simple present tense. These errors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
1
3
0
Order By: Relevance
“…For example: a student may use "when she x in home" instead of "when she is in home" or "I x lazy to study" instead of "I am lazy to study." It is supported to the research done by Siswoyo (2016), Fitria (2019), Siregar (2020) and Firmansyah (2020) which have found that omission of "be" frequently occurred in students writing. In this type of errors, it may happen as a result of the differences language system between native language and target language as same as subject-verb agreement errors occurred.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…For example: a student may use "when she x in home" instead of "when she is in home" or "I x lazy to study" instead of "I am lazy to study." It is supported to the research done by Siswoyo (2016), Fitria (2019), Siregar (2020) and Firmansyah (2020) which have found that omission of "be" frequently occurred in students writing. In this type of errors, it may happen as a result of the differences language system between native language and target language as same as subject-verb agreement errors occurred.…”
Section: Resultssupporting
confidence: 71%
“…Numerous researchers have previously done by Siswoyo (2016), Fitria (2019), Siregar (2020) which conducted a research in the same area with the Senior High School students as the subject. They tried to find out the errors made by the students in the term of writing English paper.…”
Section: Introductionmentioning
confidence: 99%
“…The errors were misformation errors. According to H. Siregar & Zuriani, (2020), The incorrect morpheme or structural form is what distinguishes these errors. It results from using words in the wrong order.…”
Section: Total Of Errorsmentioning
confidence: 99%
“…The opposite of omission errors was an addition error. It may be identified by the existence of anything that should not be in a well-written document (H. Siregar & Zuriani, 2020). The researcher found 3 errors in student errors.…”
Section: Committed By Students S3mentioning
confidence: 99%